Development of key intellectual ability to generalization within foreign language discipline - Sergeyeva, Tetyana Viktorivna; Lysenkova, Tetiana Mykhailivna; Tkachenko, Svitlana Viktorivna (MDPC Publishing, 2021)
The article deals with the problem of development of students' thinking within the framework of the foreign language discipline. The solution of intelligence development problem in the existing time frame is possible through academic disciplines due to subject tasks, the solution of which requires conscious intellectual actions that underlie one or another intellectual ability. The key intellectual ability that characterizes the level of thinking development is the ability to generalize. It is necessary for the analyst, scientist, manager, solving non -standard problems. Purposeful development of the ability to generalize is possible within the framework of any academic discipline by means of a special formulation of subject tasks for the generalization of mastered material in different formats. The article provides an example of such formats within the framework of the foreign language discipline.
Keywords: purposeful development of thinking; intellectual ability to generalize; student-centered